2019
DOI: 10.2475/06.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions by rock organic carbon oxidation and the net geochemical carbon budget of the Mackenzie River Basin

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 77 publications
3
71
0
Order By: Relevance
“…Nevertheless, the similar magnitude of the geological sources and sinks could keep the C cycle in an approximate steady-state balance over million-year timescales ( Taiwanese catchment 41,43, 59,86,93,143 (the Liwu River); and mountain catchments in Guadeloupe 144,145 . We can calculate the net rock-atmosphere CO2 flux (Jnet, tC km -2 yr -1 ) in such regions 142 Environment, 20 th April 2020, https://doi.org/10.1038/s43017-020-0058-6 For the final corrected version of the manuscript, please see the journal link, or contact the authors.…”
Section: Net 'Rock-atmosphere' Carbon Transfersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the similar magnitude of the geological sources and sinks could keep the C cycle in an approximate steady-state balance over million-year timescales ( Taiwanese catchment 41,43, 59,86,93,143 (the Liwu River); and mountain catchments in Guadeloupe 144,145 . We can calculate the net rock-atmosphere CO2 flux (Jnet, tC km -2 yr -1 ) in such regions 142 Environment, 20 th April 2020, https://doi.org/10.1038/s43017-020-0058-6 For the final corrected version of the manuscript, please see the journal link, or contact the authors.…”
Section: Net 'Rock-atmosphere' Carbon Transfersmentioning
confidence: 99%
“…Mountain building could potentially drive such transient C cycle perturbations and associated climatic change.Insights into how C cycle imbalances can arise comes from river catchments where enough data have been collected to quantify each rock-atmosphere C transfer term(Fig. 1B,and Supplementary Information): four catchments in the western Southern Alps of New Zealand69,127,139 (the Haast, Hokitika, Waiho and Whataroa Rivers); three draining the Mackenzie Basin in Canada 42,43,[140][141][142] (the Peel, Arctic Red and Mackenzie Rivers); a…”
mentioning
confidence: 99%
“…The ∆ 14 C analysis of riverine OC, carried out on samples collected from the mouth of the Arctic Great Rivers (Holmes et al, 2020) has revealed that the MRB exports on average the oldest POC (i.e., 14 C depleted) to the Arctic Ocean out of all Arctic Great Rivers, but also a mixture of aged and modern DOC (Holmes et al, 2020; Raymond et al, 2007). The prevailing hypothesis explaining these age patterns is that POC is mostly derived from petrogenic sources (Hilton et al, 2015; Horan et al, 2019) and thawing permafrost and river bank erosion (Feng et al, 2013; Vonk et al, 2015; Wild et al, 2019), while DOC contains a comparatively larger proportion of recent photosynthates derived from terrestrial vegetation (Guo et al, 2007; Marwick et al, 2015). At present, the range and variability in riverine Δ 14 C‐OC is unknown in large parts of the MRB, partly owing to the remoteness of the region and the limited network of roads allowing access to the rivers.…”
Section: Introductionmentioning
confidence: 99%
“…For M diss_Re , we excluded an initial rapid period of change of ion concentrations (Re, SO 4 2-, and Ca 2+ ), which is inconsistent with the lowland river processes we sought to model (see the Data Repository). The value of f Re provides a maximum constraint on POC petro loss due to contributions of dissolved rhenium from non-POC petro phases (Horan et al, 2019).…”
Section: Evaluating Poc Oxidationmentioning
confidence: 99%